FATIGUE LIFE PREDICTION BY THE STRUCTURALLY SENSITIVE DAMAGE INDICATOR - Karuskevich, Mikhail (Proceedings of National Aviation University, 2012)
The investigations of the new fatigue sensor that was carried out at the wide range of cyclicloads conditions show the ability of the indicator application in Structural Health Monitoringsystems of planes, bridges, vessels, and other structures. Accumulated fatigue damage may byestimated by the intensity of deformation relief, i.e. by its extrusion/intrusion and persistent slipbands structures on the indicator surface.Keywords: alelad aluminum alloys, deformation relief, fatigue, fatigue indicator.Розглянуто результати дослідження нового індикатора втоми, проведених в широкомудіапазоні режимів циклічного навантажування. Показано можливість застосування індикатора всистемах контролю технічного стану літаків, мостів, кораблів та інших конструкцій.Накопичене втомне пошкодження визначено за інтенсивності деформаційного рельєфуповерхні, який формують екструзії, інтрузії і сталі смуги ковзання на поверхні індикатора.Ключові слова: втома, деформаційний рельєф, індикатор втоми, плакований алюмінієвийсплав.